2021
DOI: 10.1016/j.dcn.2021.100984
|View full text |Cite|
|
Sign up to set email alerts
|

Preferential responses to faces in superior temporal and medial prefrontal cortex in three-year-old children

Abstract: Perceiving faces and understanding emotions are key components of human social cognition. Prior research with adults and infants suggests that these social cognitive functions are supported by superior temporal cortex (STC) and medial prefrontal cortex (MPFC). We used functional near-infrared spectroscopy (fNIRS) to characterize functional responses in these cortical regions to faces in early childhood. Three-year-old children (n = 88, M(SD) = 3.15(.16) years) passively viewed faces that varied in emotional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 98 publications
2
1
0
Order By: Relevance
“…Our success in defining face‐, scene‐, and object‐selective ssROIs complements prior studies showing that this same movie could successfully define ssROIs for regions of the theory of mind network and pain matrix in adults (Jacoby et al, 2016) and evoke distinct responses in these networks in children (Richardson, 2019; Richardson et al, 2018). Our findings also dovetail more generally with other work harnessing movie data to study predictive processing (Lee, Aly, & Baldassano, 2021; Richardson et al, 2021), event structure processing (Baldassano et al, 2017), and individual differences (Finn & Bandettini, 2021; Richardson, 2019; Vanderwal et al, 2017). Taken together, these studies highlight the power of even a very short movie to efficiently evoke a broad set of functional profiles, well beyond that possible with a traditional, highly constrained experiment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our success in defining face‐, scene‐, and object‐selective ssROIs complements prior studies showing that this same movie could successfully define ssROIs for regions of the theory of mind network and pain matrix in adults (Jacoby et al, 2016) and evoke distinct responses in these networks in children (Richardson, 2019; Richardson et al, 2018). Our findings also dovetail more generally with other work harnessing movie data to study predictive processing (Lee, Aly, & Baldassano, 2021; Richardson et al, 2021), event structure processing (Baldassano et al, 2017), and individual differences (Finn & Bandettini, 2021; Richardson, 2019; Vanderwal et al, 2017). Taken together, these studies highlight the power of even a very short movie to efficiently evoke a broad set of functional profiles, well beyond that possible with a traditional, highly constrained experiment.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to early emerging function, our study also found evidence of protracted developmental change, particularly in the faceselective pSTS, where developmental change could not be explained by a confound of increasing attention with age. This finding is consistent with work using traditional paradigms, which has found that responses to faces and socially relevant stimuli are present in pSTS by infancy and early childhood (Otsuka et al, 2007;Lloyd-Fox et al, 2009;Powell et al, 2017;Richardson et al, 2021), but undergo protracted development late into childhood (Ross, de Gelder, Crabbe, & Grosbras, 2014;Scherf et al, 2007;Walbrin, Mihai, Landsiedel, & Koldewyn, 2020) but see (Golarai et al, 2007). This work also fits with a broader literature suggesting that higher-level social regions in general, beyond the pSTS (e.g., the theory of mind network) undergo protracted development across childhood (Gweon et al, 2012;Moraczewski et al, 2018;Richardson et al, 2018;Richardson & Saxe, 2020;Saxe et al, 2009).…”
Section: Higher-level Social Functionsupporting
confidence: 90%
“…For example, fNIRS research showed that social and speech stimuli activated optodes over the pSTS in young infants (Lloyd-Fox et al, 2009. Activity in similar regions was found during naturalistic social interactions with toddlers (Hakuno et al, 2018) and when 3-year-olds viewed faces (Richardson et al, 2021). The evidence that the pSTS is activated during social interactions and social processing is corroborated by fMRI studies with adults (e.g., Deen et al, 2015;Isik et al, 2017).…”
Section: Introductionmentioning
confidence: 87%